Bodies on the Border: Between Ableist Cures, Nationalist Hostilities, and Deadly Futures - McCormack, Donna; Zakour, Lynne; Kahwagi, Richard; Young, Ingrid (Ars Medica, 2023)
This series of images emerges from a collaboration between academics and artists focused on organ transplantation and chronic illness. The images are part of the ongoing work of Capturing Chronic Illness, a project founded by UK-based medical humanities academics Donna McCormack (University of Strathclyde, UK) and Ingrid Young (University of Edinburgh, UK) to explore how arts may engage with health, illness, and non-normative embodiments that exceed dominant narratives. The exchange that produced the images is based directly on McCormack’s project, Transplant Imaginaries, which analyses fictional texts (novels and films) to explore biotechnological and anticolonial embodiments and relationalities in representations of transplantation. The three images, produced with Lynne Zakhour and Richard Kahwagi, explore transplant medicine beyond a curative imaginary. They point to key issues that are rarely discussed or even acknowledged in the clinic, but may be discussed in memoirs, by recipients and in fiction. These images, then, push us to reconsider how organ transplantation necessarily demands we pay attention to those embodied stories of living with the dead, crossing borders and how care, even that deemed "lifesaving," may be violent. Capturing Chronic Illness explores how the arts can listen to silenced or denied experiences of (particularly) queer health and illness.